2021
DOI: 10.1108/ijhma-11-2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting housing prices in Izmir, Turkey: a quantile regression approach

Abstract: Purpose The purpose of this paper is to investigate empirically the main factors that affect the house prices in Izmir, Turkey using the quantile regression and ordinary least square approaches. Design/methodology/approach Sample data about the housing market for Izmir collected from the web pages of various real estate agencies during June 2018. Following this, the quantile regression method is used to estimate all possible effects of variables on each interested quantile to determine the factors that affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Moreover, Yusof and Ismail (2012) found that location-related attributes have the strongest effect on property prices. Finally, Özsoy and Şahin (2021) are of the same opinion that location has a uniform impact on apartment prices. This finding has an implication for real estate developers and investors in Prishtina, who should understand that Prishtina is a mono-centric city and that any distance from the city center affects the prices of the apartments.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, Yusof and Ismail (2012) found that location-related attributes have the strongest effect on property prices. Finally, Özsoy and Şahin (2021) are of the same opinion that location has a uniform impact on apartment prices. This finding has an implication for real estate developers and investors in Prishtina, who should understand that Prishtina is a mono-centric city and that any distance from the city center affects the prices of the apartments.…”
Section: Discussionmentioning
confidence: 98%
“…In like manner, size is an important structural variable in property prices (Aziz et al , 2020). Above all, Özsoy and Şahin (2021) in their study found that the size of the house, the existence of an elevator, fire and security have a positive and significant effect on prices. Finally, the size and age of the building are considered to be important structural attributes affecting apartment prices (Shetty et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…In terms of medical care, Wang et al's [24] research on several megacities in China finds that hospitals near communities are positively correlated with housing values; the farther away from the hospital, the lower the value of the house [25].…”
Section: Literature Reviewmentioning
confidence: 99%